Penerapan Sistem Irigasi Otomatis Berbasis IoT: Analisis Perbandingan Efisiensi Sensor Kapasitif dan Sensor Resistif dalam Pertanian Presisi - Dodi Yudo Setyawan; Nurfiana Nurfiana; Retno Dwi Handayani; Lia Rosmalia (Politeknik Negeri Sriwijaya, 2026)
This study compared the accuracy and efficiency of capacitive and resistive soil moisture sensors within an Internet of Things (IoT) based automated irrigation system in a smart garden case study.Irrigation automation by factors such as soil moisture sensors reliable as required, is a critical determinant in efficient water use.The paper uses the ESP32 based IoT irrigation framework to evaluate performance of two soil moisture sensors: capacitive and resistive. The operational efficiency, as well as the difference in total cost is also looked at.Smart gardens were used in this paper to record over three months (from July until September) dynamics of soil humidity, as well as the consumption of water. The cloud-based database saved in real-time per sensor response on one hand information, and then further statistical data every hour about pump activation frequency and total water discharge.Conclusions drawn from quantitative analysis are: Resistive sensor performance has some major problems, such as excessive sensitivity to changes in soil conductivity and a drift tendency over time. This causes Irrigation pump false alarms to occur frequently. Conversely, the capacitive sensor offered readings with more stable repetition and smaller variation.The results show that, compared to the resistive-based system, the system with capacitive sensors reduced cumulative water consumption by 30%. This implies that although resistive sensors may have a lower initial cost, the long-term water use efficiency which can be attained with capacitive sensors easily compensates for any disadvantages in performance they may have and makes their installation the best choice for sustainable IoT-based precision agriculture applications.